Mobile social network in proximity: taxonomy, approaches and open challenges. Issue 1 (7th April 2015) - Chang, Chii; Srirama, Satish Narayana; Ling, Sea
Abstract : Purpose: – Recent smart mobile devices are capable of letting users produce various digital content, and share/upload the content to many social network services (SNS) directly via wireless network connections. The phenomenon has increased the number of people using mobile SNS applications. Although the applications have become more popular, mobile users have been restricted in the virtual communities of online SNS and are not aware of the social opportunities available to them in real-time surrounding. While they spend most of their time accessing online SNS, they have missed many opportunities to interact with others for new friendships, business opportunities or information sharing. Consequently, a new breed of mobile social network (MSN) system has arisen to assist mobile users to interact with proximal people and perform various social activities. Such a proximal-based MSN environment is termed a Mobile Social Network in Proximity (MSNP). Design/methodology/approach: – Developing an MSNP system needs to address a number of issues and challenges, such as heterogeneity, content/service discovery, privacy and trust, resource management, and so on. This paper identifies and describes these challenges, and reviews a number of related solutions from existing literature. In the follow up, this paper addresses a number of open challenges in the MSNP domain. Findings: – Although various works have been proposed to enable and overcome challenges in MSNP, there are still many unsolved open challenges in terms of identification, content management, social-aware discovery, trust in public environment, adaptation, quality of service and the development of MSNP. We have addressed these challenges in this paper as future research directions in the MSNP domain. Originality/value: – This paper provides an original literature review in MSNP and identifies a number of open challenges as research direction in the MSNP domain.